Global COVID-19 Pandemic: Implemented Policies and Effective Measures Employed Worldwide - Ghaleb, Belal Dahiam Saif (PT FORMOSA CENDEKIA GLOBAL, 2024)
In this article, a comprehensive methodology has been used to investigate the policies and measures taken around the world in the fight against the Covid-19 pandemic. Research includes examining international reports, official government statements, and scientific literature from organizations such as the World Health Organization (WHO). Analysis and synthesis of these resources were made to identify common trends, challenges and effective strategies used in different countries and regions. The methodology aims to provide a comprehensive overview of the global response to the Covid-19 pandemic, to provide insights into the effectiveness of these various policies and measures by addressing the measures taken and policies implemented in response to the COVID-19 pandemic. Then, he discussed the countries struggling with the covid-19 pandemic on a country basis and explained the policies and measures they took.